Utility of a Team-Based Multimodal Opioid Reduction Protocol for the Pediatric Plastic Surgery Population. (May 2020) - Crowley, Jiwon Sarah; Hsieh, Sun; Gabriel, Rodney A.; McLean, Paige; Gosman, Amanda; Lance, Samuel
Abstract : Abstract: Opioid use can cause significant adverse side effects with increased propensity toward both short- and long-term complications in the pediatric population. We present a multifaceted opioid reduction protocol based on physician and care team member education. The strategy was designed to alter prescribing practices, improve preoperative and postoperative patient education, increase the use of nonnarcotic pain control modalities, and improve coordination of opiate reduction strategies for all team members participating in patient care. We present the utility of this strategy in limiting postoperative narcotic use in the pediatric plastic surgery population. A prospective study with historical controls was conducted to evaluate pediatric patients undergoing elective pediatric plastic surgery procedures at 3-month intervals in 2016, 2017, and 2018. In the final year, the dedicated opiate reduction protocol was implemented before the data collection period, and results were compared with the prior 2 collection periods. The primary outcomes were total days and doses of outpatient narcotics prescribed after surgery. The median days (quartiles) of opioids prescribed in 2016, 2017, and 2018 cohorts were 1.5 (1.1, 2.5) days, 1.5 (1.4, 2.5) days, and 0.8 (0, 1.6) days, respectively. The median doses (quartiles) of opioids prescribed in 2016, 2017, and 2018 cohorts were 6.3 (6, 10), 6.0 (5.7, 15.0), and 4.2 (0, 6.2) doses, respectively. There were statistically significantly less days and doses of opioids prescribed in the 2018 cohort when compared with the 2016 ( P < 0.0001) and 2017 ( P < 0.0001) cohorts. A multimodal opioid reduction protocol was successfully implemented for the pediatric plastic surgery population. Patients were able to shorten the duration of narcotic prescription upon discharge with the use of a multidisciplinary team approach.